Edukasi isi piringku dan Demo Masak Sea Dimsum Sumber Protein Hewani pada Anak Sekolah di Panti Asuhan Gotong Royong - Fayasari, Adhila; Zahrani Astuti, Elsa; Yasfa Aulia, Hunalika; Yudhowanti, Septiajati; Harjito, Zaneta; Assyifa, Aulia; Salsabila, Delia (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Adolescents are vulnerable to nutritional issues such as undernutrition and overnutrition, which can affect their physical and cognitive development. Balanced nutrition is essential, particularly for children in orphanages, who often face challenges in accessing nutritious food and health education. Objective: This community service aimed to improve knowledge and awareness about "Isi Piringku" and the importance of consuming animal protein among school-aged children at the Gotong Royong Orphanage, Bantul, Yogyakarta. Method: The program involved 22 children aged 6–15 years and their caregivers. Activities included pre-surveys, nutritional status assessments, interactive education sessions combining lectures, videos, games, and a hands-on demonstration of making Sea-Dimsum enriched with animal protein. Pre- and post-tests measured knowledge levels before and after the intervention. Results: The educational intervention significantly improved knowledge, with good knowledge scores rising from 57% pre-test to 87% post-test. The Sea-Dimsum demonstration engaged participants, fostering a practical understanding of balanced nutrition. Challenges included varying comprehension levels due to age differences, affecting knowledge retention among younger participants. Conclusion: The program effectively increased nutritional knowledge by 30%, emphasizing the importance of balanced diets and animal protein. Future initiatives could include diverse nutritional topics, such as interpreting food labels and selecting healthy snacks, to further enhance nutrition literacy and health outcomes.